2017
DOI: 10.1002/2016jg003614
|View full text |Cite
|
Sign up to set email alerts
|

Human impact on long‐term organic carbon export to rivers

Abstract: Anthropogenic landscape alterations have increased global carbon transported by rivers to oceans since preindustrial times. Few suitable observational data sets exist to distinguish different drivers of carbon increase, given that alterations only reveal their impact on fluvial dissolved organic carbon (DOC) over long time periods. We use the world's longest record of DOC concentrations (130 years) to identify key drivers of DOC change in the Thames basin (UK). We show that 90% of the long‐term rise in fluvial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 115 publications
(134 reference statements)
0
49
1
Order By: Relevance
“…Given the population connected to main sewerage reported in this study, this would give a per capita figure of contribution of carbon from sewage effluent discharge of 4.1 kg C/ca/year, that is, considerably larger than the value found in this study. Noacco et al () studied a 130‐year record of DOC concentration and flux from the River Thames and showed that, although there were short‐term increases in DOC concentration due to land‐use change, the most important driver of change was increasing discharge from STWs as the population of the catchment increased. Even with advances in sewage treatment, the increased amount of water coming into the catchment via STWs caused increased DOC concentration in the river.…”
Section: Discussioncontrasting
confidence: 77%
See 3 more Smart Citations
“…Given the population connected to main sewerage reported in this study, this would give a per capita figure of contribution of carbon from sewage effluent discharge of 4.1 kg C/ca/year, that is, considerably larger than the value found in this study. Noacco et al () studied a 130‐year record of DOC concentration and flux from the River Thames and showed that, although there were short‐term increases in DOC concentration due to land‐use change, the most important driver of change was increasing discharge from STWs as the population of the catchment increased. Even with advances in sewage treatment, the increased amount of water coming into the catchment via STWs caused increased DOC concentration in the river.…”
Section: Discussioncontrasting
confidence: 77%
“…Even with advances in sewage treatment, the increased amount of water coming into the catchment via STWs caused increased DOC concentration in the river. In the study period considered by Noacco et al (), transient DOC concentrations from increasing population rose from 1.5 mg/L in 1884 to 4.1 mg/L in 2005, with 90% of the long‐term trend in increased DOC concentrations being explained by the rise in C inputs from population growth and urban expansion ( p < 0.001). Over the same period, the population of the Thames rose from 911,000 and 3.7 million, which indicates a change in per capita export from 3.46 to 2.28 kg organic C per person, per year; that is, there was an increased rate of removal, but this was not weighed by the increase in population using STWs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Carbon export from terrestrial ecosystems into drainage networks is controlled by hydrological 295 regime, geomorphological landscape, biogeochemical processes, and human impact within the catchment of concern (Noacco et al, 2017;Stimson et al, 2017). Affected by sparse vegetation coverage, both DOC and POC contents in the Wuding catchment were relatively low compared with most rivers in the world.…”
Section: Discussion 41 Carbon Export Dynamics Within the Catchmentmentioning
confidence: 99%